1999
DOI: 10.1210/jcem.84.10.6028
|View full text |Cite
|
Sign up to set email alerts
|

7α-Methyl-19-Nortestosterone Maintains Sexual Behavior and Mood in Hypogonadal Men*

Abstract: The synthetic steroid 7alpha-methyl-19-nortestosterone (MENT) is a potent androgen that is resistant to 5alpha-reductase. It thus has decreased activity at the prostate and may have advantages over testosterone-based regimens in long term treatment or as part of a male contraceptive. Administration to eugonadal men results in suppression of gonadotropins, but its ability to support androgen-dependent behavior has not been investigated. For sustained release administration, MENT acetate was used, because its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…However, during testosterone replacement therapy in hypogonadal men, the positive mood scale improved significantly in both groups and the negative mood scale improved in the second comparison group. This change in mood had been previously reported by Burris et al (1992), Anderson et al (1999), O'Connor et al (2002) using other questionnaires as well as Wang et al (1996b, 2000) using this diary. We note that these changes in mood were not correlated with change in testosterone levels from baseline or value of testosterone levels after 30 days of treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, during testosterone replacement therapy in hypogonadal men, the positive mood scale improved significantly in both groups and the negative mood scale improved in the second comparison group. This change in mood had been previously reported by Burris et al (1992), Anderson et al (1999), O'Connor et al (2002) using other questionnaires as well as Wang et al (1996b, 2000) using this diary. We note that these changes in mood were not correlated with change in testosterone levels from baseline or value of testosterone levels after 30 days of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…The exact relationship between androgens and mood is less clear. Studies have shown that testosterone replacement therapy improves the general well‐being and the mood states of hypogonadal men (O'Carroll et al, 1985; Wang et al, 1996b; Anderson et al, 1999; Wang et al, 2000; O'Conner et al, 2002). Others failed to demonstrate this positive effect of testosterone on mood (Davidson et al, 1979).…”
mentioning
confidence: 99%
“…SARMs that are not 5α-reductase substrates or form DHT-like derivatives with weak androgenic activity have low androgen action in prostate [109, 189, 201, 212, 245, 301, 342]. A promising SARM in this category is 7α-methyl-19-nortestosterone, commonly called MENT [224, 301, 342], which was developed by the Population Council and is currently in clinical trials as an androgen therapy for hypogonadal men [11, 345]. MENT shows low androgen activity in prostate but is more potent than T in other peripheral androgen-responsive tissues including bone [77, 301, 342] and muscle [77, 301, 342].…”
Section: Emerging Strategies Of Hormone-related Therapies In Alzhmentioning
confidence: 99%
“…On the other hand, Anderson et al. [142] found that the administration of 7α‐methyl‐19‐nortestosterone (MENT) also improves NPT in hypogonadal men from Edinburgh. However, MENT cannot be metabolized through the 5α‐pathway to 5α‐metabolites.…”
Section: Approaches For the Amelioration Of Sres In Hypogonadal Men Bmentioning
confidence: 99%